Larutan Tape Singkong (Manihot utilissima) sebagai Atraktan Nyamuk - Eva Mai Sa’adah; Isnawati Isnawati; Noraida Noraida (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Influence of Fermented Cassava (Manihot utilissima) Solutions as Atraktan in Mosquito Trap on The Number of Mosquitoes Trapped. The use of synthetic insecticides can cause health hazards to humans. Mosquito trap made of disused plastic bottles plus mosquito atraktan from natural materials is an alternative that is more economical, safe and environmentally friendly. One of the mosquito atraktan compounds is CO2. Fermented cassava is potentially as mosquito atraktan because it can produce CO2. This study aimed to know the influence of fermented cassava solutions as atraktan in mosquito trap from plastic bottles on the number of mosquitoes trapped. Type this study was Quasi Experiment. Design this study was Post-test Only with Control Design. The concentration of fermented cassava solutions was used in this study was 0% (control), 10%, 30%, 50% and 70%. The results showed the number of mosquitoes trapped at a concentration of 0% (control), 10%, 30% and 70% as much as 0 tail, whereas the konentrasi 50% as much as 1 tail. Kruskal Wallis test results showed no significant effects of the concentration of fermented cassava solutions.